How Does Socio-Economic Status Shape a Child's Personality? - Thomas Deckers; Armin Falk; Fabian Kosse; Hannah Schildberg-Hörisch (Institute for the Study of Labor (IZA), 2015)
We show that socio-economic status (SES) is a powerful predictor of many facets of a child's personality. The facets of personality we investigate encompass time preferences, risk preferences, and altruism, as well as crystallized and fluid IQ. We measure a family's SES by the mother's and father's average years of education and household income. Our results show that children from families with higher SES are more patient, tend to be more altruistic and less likely to be risk seeking, and score higher on IQ tests. We also discuss potential pathways through which SES could affect the formation of a child's personality by documenting that many dimensions of a child's environment differ systematically by SES: parenting style, quantity and quality of time parents spend with their children, the mother's IQ and economic preferences, a child's initial conditions at birth, and family structure. Finally, we use panel data to show that the relationship between SES and personality is fairly stable over time at age 7 to 10. Personality profiles that vary systematically with SES might offer an explanation for social immobility.
Keywords: C90; D64; D90; D81; J13; J24; J62; 330; personality; human capital; risk preferences; time preferences; altruism; experiments with children; origins of preferences; social immobility; socio-economic status